The Effect of high intensity interval training on serum levels of Osteopontin and insulin resistance index in sedentary overweight and obese women - Naemeh Dashti; Najmeh Rezaeian; Maryam Karimi; Negar Kooroshfard (Shahid Beheshti University, 2021)
Purpose: Osteopontin is a novel adipose tissue derived cytokine correlating with obesity and its related metabolic diseases such as insulin resistance and type II diabetes. The purpose of this study was to investigate effect of high intensity interval training (HIIT) on serum levels of Osteopontin, insulin and fasting glucose and insulin resistance index (HOMA-IR) in young sedentary overweight and obese women.Methods: Twenty overweight and obese women randomly divided into two groups including experimental (mean age 32.5 ± 4.14 years, body mass index 33.18 ± 6.12 Kg/m2) and control (mean age 35.45 ± 2.33 years, body mass index 31.58 ± 1.65 Kg/m2). Subjects in experimental group participated in eight weeks of HIIT (one minute of running interval at intensity of 90 percent of maximal heart rate and one minutes of rest interval of running at intensity of 50-60 percent of maximal heart rate, 10 sets per session, 20 minutes per session, three times per week). Blood factors and body composition indices were assessed before and after training protocol. Statistical analysis was done by Covariance, paired t-test and Pearson correlation at significant level of P < 0.05.Results: According to paired t-test, HIIT resulted in significant decrease in serum levels of osteopontin (P = 0.0001) and weight (P = 0.0001), body mass index (P = 0.0001) and body fat percent (P = 0.0001) in post-test compared to pre-test. However, Covariance showed that only changes in levels of insulin (P = 0.039), weight (P = 0.001), body mass index (P = 0.005) and body fat percent (P = 0.0001) were significantly different between training and control groups. Moreover, there were negative correlation between changes in osteopontin level and changes in body mass index (P = 0.0001) and body fat percent (P = 0.044).Conclusion: High intensity interval training (HIIT) decreased osteopontin level and improved body composition and metabolic status, and therefore, can be suggested as a therapeutic procedure in obese and overweight young women.